2013
DOI: 10.1371/journal.pntd.0002427
|View full text |Cite
|
Sign up to set email alerts
|

Public Acceptance and Willingness-to-Pay for a Future Dengue Vaccine: A Community-Based Survey in Bandung, Indonesia

Abstract: BackgroundAll four serotypes of dengue virus are endemic in Indonesia, where the population at risk for infection exceeds 200 million people. Despite continuous control efforts that were initiated more than four decades ago, Indonesia still suffers from multi-annual cycles of dengue outbreak and dengue remains as a major public health problem. Dengue vaccines have been viewed as a promising solution for controlling dengue in Indonesia, but thus far its potential acceptability has not been assessed.Methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
86
4
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 32 publications
16
86
4
6
Order By: Relevance
“…After reading the full texts, five additional papers regarding vaccine acceptance were excluded because they did not provide sufficient data for calculation of OR95%CI. Therefore, two studies regarding dengue vaccine acceptance were included in the meta-analysis (12,13). While, all papers (eight papers) regarding WTP for dengue vaccine were excluded because they were not qualified to calculate OR95%CI.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After reading the full texts, five additional papers regarding vaccine acceptance were excluded because they did not provide sufficient data for calculation of OR95%CI. Therefore, two studies regarding dengue vaccine acceptance were included in the meta-analysis (12,13). While, all papers (eight papers) regarding WTP for dengue vaccine were excluded because they were not qualified to calculate OR95%CI.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In total, 1151 participants from two studies regarding dengue vaccine acceptance were identified (12,13) Evidence for heterogeneity between studies was found in the attitude towards dengue variable (P = 0.051); therefore, the data were assessed using random effect model. Evidence for heterogeneity was not found regarding other variables including attitude towards vaccination (P = 2…”
Section: Quantitative Data Synthesis and Source Of Heterogeneity Regamentioning
confidence: 99%
See 3 more Smart Citations